Hands-On Workshops Improve Emergency Department Physicians' Self-Reported Understanding of Pediatric Hand Injuries. Issue 2 (February 2022) - Market, Marisa; Zhu-Pawlowsky, Julia; Bhatt, Maala; Cheung, Kevin
Abstract : Objectives: The aims of this study were to assess emergency department (ED) physician perception of hand injuries and improve their understanding and confidence in treating these injuries. Methods: Combined didactic and hands-on workshops for ED physicians were developed and run by a team of medical students, plastic surgeons, and ED physicians. The workshops consisted of a short review by a hand surgeon followed by hands-on sessions involving radiograph assessment, administration of local anesthetic, closed reduction, and splinting. Two sessions, 6 months apart, were provided. The workshops were evaluated using preworkshop and postworkshop questionnaires to assess the following domains: confidence and competence in treating hand injuries, knowledge of basic hand injury care, and feedback on the intervention itself. Results: Fifty physicians participated in the workshops. After the workshops, physician recognition of hand fracture reduction as a critical skill increased. Self-efficacy ratings of fracture assessment, administration of local anesthetic, performing a reduction, and applying postreduction immobilization increased. Median scores on knowledge-testing questions also increased postintervention from 73.3% (95% confidence interval, 70.2–78.5) to 86.7% (95% confidence interval, 79.3–86.2) ( P < 0.05). Finally, physicians reported that they found the intervention educational, useful, and important, and approximately 90% of participants indicated they intended to change their practice based on this intervention. Conclusions: Knowledge sharing between specialists and generalists through combined didactic and hands-on workshops is an effective and well-received method of refining physician knowledge and increasing confidence in treating subspecialty-specific clinical presentations. Abstract : Supplemental digital content is available in the text.